El dinamismo de la frontera valenciana en el siglo XIII: El papel de la corona, la red parroquial y los repobladores en el territorio = The Dynamism of the Valencian Frontier in the 13th Century: The Role of the Crown, the Parish Network and the Repopulation of the Territory - Cardells Martí, Francesc A. (Isidorianum, 2025)
One explanation of the border area of Valencia is the spiritual one formed by a network of parishes and religious centres but also by the traditions of the new settlers and their recent history which is combined with the historical past of the region. In short, different levels of transformation that will give rise to the specificity of the kingdom of Valencia.